Problem solving - Mackall, Dandi Daley; Ferguson Publishing (New York : Ferguson, 2009)
'Developing and understanding different methods of tackling problems is an essential career skill. Problem Solving, Third Edition teaches readers how to become a problem solver, a valuable and highly sought person in today's complicated workforce.'--Amazon.com.
Rev ed. of : Problem solving / Dandi Daley Mackall, 1998
Includes bibliographical references (p. 177-180) and index
Keywords: Vocational guidance -- Juvenile literature; Problem solving -- Juvenile literature; Career development -- Juvenile literature; High school graduates -- Employment -- Juvenile literature; Vocational guidance; Problem solving; High school graduates -- Employment